Reverse poly(butylene oxide)–poly(ethylene oxide)–poly(butylene oxide) block copolymers with lengthy hydrophilic blocks as efficient single and dual drug-loaded nanocarriers with synergistic toxic effects on cancer cells. Issue 64 (12th July 2015) - Villar-Alvarez, E.; Figueroa-Ochoa, E.; Barbosa, S.; Soltero, J. F. A.; Taboada, P.; Mosquera, V.
<x xml:space="preserve">Abstract</x> Reverse triblock copolymer micelles with lengthy polyethylene oxide blocks as efficient sustained dual drug-loaded nanocarriers.